O efeito da impulsividade em aspectos motores e cognitivos em diferentes condições de uma tarefa de apontamento - Bárbara de Paula Ferreira (2023)
Despite impulsivity being widely reported in its dysfunctional aspect by the literature, there is evidence that non-pathological impulsivity has positive effects on motor behavior in certain contexts. Based on previous studies, it is speculated that motor tasks that require less cognitive effort and high space-time pressure may favor the motor performance of individuals with higher impulsivity. Conversely, motor tasks that demand higher cognitive effort and low temporal pressure may favor the performance of individuals with lower impulsivity. In order to investigate this possible relationship, the present study aimed to investigate the effect of impulsivity on motor control and cognitive effort in different aiming tasks. We had an initial sample of 109 right-handed participants of both sexes, with a mean age of 23.35 ± 3.33 years. The BIS-11 scale was used to classify the level of impulsivity. Participants who did not meet the scoring criteria to be allocated to the more impulsive group (GI+) or less impulsive group (GI-) were excluded from the final sample. The participants from the GI+ group (n= 31) and GI- group (n= 32) performed two conditions of a aiming task that required lower and higher cognitive demand. To assess the level of cognitive effort demanded by the task conditions, an electroencephalogram was used. Variables related to time, accuracy, kinematics, and inhibitory control were analyzed to infer motor performance and control, and cognitive variables were analyzed to infer the level of cognitive effort. The results indicated that motor performance and kinematic profile were similar between groups in both task conditions. In the cognitive variables, the GI+ group showed a higher workload index than the GI- group in both conditions. From the results, it is possible that the increase in cognitive effort is used as a compensatory mechanism by individuals with higher impulsivity. This possible compensatory mechanism can be considered functional since it allows individuals with higher impulsivity to achieve similar motor performance levels to those of individuals with lower impulsivity in unfavorable practice contexts.